Instrument wetting errors in hurricanes and a re-examination of inner-core thermodynamics - Eastin, Matthew D., author (Colorado State University. Libraries, 1999)
Thermodynamic errors caused by instrument wetting are thoroughly examined and are accurately removed from 579 radial legs of aircraft flight-level data in 27 hurricanes. Similar to previous studies, a radiometer is used to provide accurate temperatures in clouds and precipitation where immersion thermometers and cooled-mirror hygrometers typically experience large errors induced by instrument wetting. Theoretical temperature errors caused by the presence of hydrometeors in the sampled air are reviewed and discussed for each instrument. A correction method is developed to remove a time-dependent bias from the radiometer temperatures using data in clear air and adjust supersaturated dew points to the equivalent of 99 percent relative humidity. In contrast to previous studies, clear air is defined using dew point depression and aircraft roll rather than the absence of liquid water. The resulting radiometer temperatures and adjusted dew points are shown to be free of instrument wetting errors and accurate. Instrument wetting locations (IWL) are identified in roughly 50 percent of the radial legs, but are more frequent in intense (Category 3, 4, and 5) hurricanes than in minimal (Category 1 and 2) hurricanes and were comprised of larger temperature errors. The maximum temperature error, liquid water content, and radial extent of each IWL is highly variable, but the majority of IWL are located in cloudy updrafts associated with eyewall and rainband<l convection, and extend less than 15 km radially. Theoretical temperature errors are rarely achieved, however, average IWL temperature errors are significant and range with height from 1.0 to 4.5°C. The temperature errors, combined with average specific humidity (q) errors ranging from 1.0 to 2.0 g kg-1, result in virtual temperature (Tv) errors ranging from 1.5 to 5.0°C and equivalent potential temperature (Oe) errors ranging from 5 to 11 K. In the eyewall average temperature and specific humidity errors range with height from 0.5 - 2.0°C and 0.5 - 1.0 g kg-1 respectively. Errors of such magnitudes can have a significant effect upon thermodynamic calculations in a near convection. Various aspects of hurricane thermodynamics are thus re-examined. Radial composites about the eyewall Radius of Maximum Updraft (RMU) indicate that after instrument wetting errors are removed: the eyewall temperature is equivalent to 50-70 percent of the total anomaly observed from the environment; specific humidity maxima are located in the eyewall but are nearly equivalent to values in the eye; and eyewall Oe is 0-5 K lower than values in the eye. The composite eyewall is shown to be moist-adiabatic with height to a first approximation and better represented by pseudo-adiabatic, rather than reversible, ascent. Average eyewall Oe for minimal and intense hurricanes are 351 K and 360 K respectively, with maximum values near 385 K. Instrument wetting errors are shown to significantly affect calculations of thermal wind balance. Finally, surface temperatures and pressures are estimated beneath the eyewall. The ratio of eyewall surface pressure to minimum central pressure is 1.02 on average. The estimated average air-sea temperature difference (SST-Ta) beneath nearly-saturated eyewalls is 2°C with maximum values near 5°C. However, the air-sea temperature difference tends to decrease toward 1°C as hurricane intensity increases.
August 1999.
Also issued as author's thesis (M.S.) -- Colorado State University, 1999.
NSF ATM-9616818 and NOAA/CIRA NA67RJ0152 on cover.
Keywords: Hurricanes; Meteorological instruments